2014
DOI: 10.1103/physreva.89.062318
|View full text |Cite
|
Sign up to set email alerts
|

Sensitivity of entanglement decay of quantum-dot spin qubits to the external magnetic field

Abstract: We study the decay of entanglement of quantum dot electron-spin qubits under hyperfine interaction mediated decoherence. We show that two qubit entanglement of a single entangled initial state may exhibit decay characteristic of the two disentanglement regimes in a single sample, when the external magnetic field is changed. The transition is manifested by the supression of time-dependent entanglement oscillations which are superimposed on the slowly varying entanglement decay related to phase decoherence (whic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
29
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(30 citation statements)
references
References 68 publications
1
29
0
Order By: Relevance
“…The results for C(t) and t D (Ω) in the thermal bath case were previously obtained in Ref. 80, where it was suggested that a measurement of t D can be used for sensing of small magnetic fields, while in Refs. 115 and 116 the possible significance of entanglement dynamics for the operation of chemical magnetometers was discussed.…”
Section: Entanglement Dynamics Due To Coupling To Thermal and Partmentioning
confidence: 69%
See 2 more Smart Citations
“…The results for C(t) and t D (Ω) in the thermal bath case were previously obtained in Ref. 80, where it was suggested that a measurement of t D can be used for sensing of small magnetic fields, while in Refs. 115 and 116 the possible significance of entanglement dynamics for the operation of chemical magnetometers was discussed.…”
Section: Entanglement Dynamics Due To Coupling To Thermal and Partmentioning
confidence: 69%
“…where K Q σξ,ξ ′ σ ′ (t) encapsulates the influence of the environment on the evolution of the reduced density matrix of qubit Q. The above representation 80,105,106 is of course closely related to the operator-sum (Kraus) representation of evolution ofρ Q , but it is much more convenient to use when the number of relevant Kraus operators is large (as it is the case here). The K functions have the following structure:…”
Section: A General Formalism In the Case Of Free Evolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially im portant in the m easurem ent o f nanostructures em bedded in the solid state, w here decoherence resulting from the interaction with the environm ent is unavoidable. A lthough decoherence typically leads to the destruction o f quantum effects, there are som e situations when decoherence can be helpful (e.g., to facilitate electron transport in quantum -dot (QD) chains [3,4]) and may even be utilized for m easurem ent purposes [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…as a measure of entanglement for the class of systems described previously, or, more generally, for any state that can be written in the form (3), as such states can be sometimes obtained for different classes of Hamiltonians under specific conditions for the initial state [35]. Here a and b are the coefficients of the initial qubit superposition, while the function…”
mentioning
confidence: 99%